Smoke and Mirrors: How Much Do We Know? An Assessment of Graduate Nursing Students' Knowledge of Tobacco and E-Cigarette Use - Pittala, Danielle; Bartos, Susan (Building Healthy Academic Communities Journal, 2020)
Background: Research suggests that there is a gap in knowledge of healthcare workers and graduate healthcare students on tobacco and e-cigarette use (Franks, Hawes, McCain, & Payakachat, 2017). These products are proving to be more addictive and contain more nicotine than traditional cigarette products. Furthermore, there is a difference in the way providers must assess patients for tobacco versus electronic cigarette (e-cigarette) use, as language plays an important role in how individuals identify as e-cigarette or traditional cigarette users (Young-Wolff et al., 2017). Although these products are new and long-term effects remain unknown, evidence suggests these products do affect overall health. Aim: The objective of this study is to assess the knowledge of graduate nursing students at Fairfield University on tobacco and e-cigarette use. Methods: Sixty-five participants were recruited from the Fairfield University graduate nursing program. Students completed a consent form followed by a pretest that contained 10 survey questions in a true or false format. An educational session was then conducted and followed by the same survey as a posttest. Data was analyzed with SPSS. Results: The mean pretest score was 61.8% and the mean posttest score was 78.8%. A paired sample t-test revealed a p-value of <0.00. Conclusion: This project was statistically significant in educating graduate nursing students on tobacco and e-cigarette use. More education is needed at the graduate level on this topic.